1988
DOI: 10.1111/j.1469-8137.1988.tb00278.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Armeria maritima (Mill.) Willd. and Plantago maritima L. from an Irish salt marsh to nitrogen and salinity

Abstract: SUMMARYTwo experiments on the interaction between salinity and nitrogen supply were carried out on the halophytes Armeria maritima and Plantago maritima. Water potential values ranged from -016 MPa to -5-OMPa and nitrogen from 028 to 280 mg 1"' N. An increase in nitrogen above 2 8 mg T' N in the medium in all cases resulted in an increase in growth, though this was not so great at higher salinities. Armeria growth rate was optimal at a higher nitrogen concentration than Plantago and Armeria also accumulated ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…In Na-accumulating halophyte species, Na + is stored in vacuoles of mesophyll cells [ 51 ], and there is an experimental evidence that surplus K + is also stored in vacuoles, both regulating osmotic potential and acting as the main cellular reserve of K + [ 58 ]. Earlier it was shown that A. maritima plants from salt marsh redistributed K + from shoots to roots with increasing salinity [ 59 ], but no such response was found in the present study in spite of significant decrease of K + concentration in leaves ( Figure 7 ).…”
Section: Discussioncontrasting
confidence: 89%
“…In Na-accumulating halophyte species, Na + is stored in vacuoles of mesophyll cells [ 51 ], and there is an experimental evidence that surplus K + is also stored in vacuoles, both regulating osmotic potential and acting as the main cellular reserve of K + [ 58 ]. Earlier it was shown that A. maritima plants from salt marsh redistributed K + from shoots to roots with increasing salinity [ 59 ], but no such response was found in the present study in spite of significant decrease of K + concentration in leaves ( Figure 7 ).…”
Section: Discussioncontrasting
confidence: 89%
“…The expansion of Plantago maritima (sea plantain) follows a near identical pattern to that of P. lanceolata. It is a stress-tolerant species that thrives on nitrogen-rich soils (Sheehy Skeffington and Jeffrey, 1988) and at Lambi in the Faroe Islands the plant increases in abundance in association with cultivation from what appears to be the onset of the settlement period (Jóhansen, 1979). It seems likely, therefore, that this species could expand in both arable and pastoral situations.…”
Section: Permanent Settlement (Ca Mid-11th Century-ad-1341)mentioning
confidence: 99%